Five decades of crop production in Odisha (1970-2020): Disentangling growth drivers of major field crops through decomposition analysis - Tripathy, P P; Mishra, S N; Bhoi, P B; Rout, R K; Anshuman, J; Nayak, C; Dwibedi, S K; Das, S; Gupta, A K (Plant Science Today, 2025)
Despite numerous studies on agricultural growth in India, there remains a critical gap in understanding long-term, crop-specific growth dynamics and their underlying drivers in climatically vulnerable states like Odisha. Paddy, green gram, and groundnut are the major field crops of Odisha, occupying the majority of the cultivated area. This study aims to analyse the long-term growth trends and production dynamics from 1970 to 2020, using secondary data to estimate compound annual growth rates (CAGR) at both overall and decadal periods. It employs an additive decomposition method to quantify the contributions of area, yield and interaction effects on change in production for revealing complex, non-linear crop-specific patterns. In the case of paddy, production grew with CAGR of 1.76 %; it was predominantly driven by yield improvements despite slight decline in area. Green gram displayed volatile trends with periods of stagnation and recovery. Notably, a production surge in the period from 1990 to 2000, which was due to combined area expansion and yield gains, followed by yield led growth in 2010-2020. Groundnut experienced growth phases, shifting from area led expansion in early decades to yield driven resurgence post 2000, aided by high-yielding, resilient varieties and enhanced extension services, though area contraction in the last decade tempered overall gains. The findings emphasize the importance of balanced strategies to stabilize the area under cultivation and promote yield enhancement through technological interventions and policy support, essential for sustainable agricultural resilience amid climatic variability and socio-economic challenges in Odisha.